2007
DOI: 10.1055/s-2007-957341
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Peroxidase and Catalase Activities and Modulation of Hydrogen Peroxide Level by Inositol Phosphoglycan-like Compounds

Abstract: Inositol phosphoglycan-like compounds are produced by the hydrolysis of the membrane bound glycosyl phosphoinositides. Besides being short term mediators of insulin action, they inhibit peroxidases and catalase, increasing the concentration of cellular hydrogen peroxide. Although high concentrations of hydrogen peroxide are toxic, moderate increases of its basal level are signals for different metabolic pathways. The inhibitor, localized in the cytosol of the cell, acts on peroxidases and catalase of the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The Nox‐dependent ROS production may be supported by impaired ROS degradation. Interestingly, phosphoinositolglycans prepared from plants and bacteria have been shown to inhibit the peroxidase and haeme‐containing catalase in non‐competitive fashion ( Thomasz et al ., 2007 ). Strikingly, similar phosphoinositolglycan structures may be released from the GPI anchors of GPI‐proteins, such as Gce1 and CD73, upon lipolytic cleavage by the GPI‐PLC ( Stralfors, 1997 ; Jones and Varela‐Nieto, 1998 ), which is apparently activated by palmitate, glimepiride and H 2 O 2 ( Müller et al ., 1993 , 1994a , 2008c ; Movahedi and Hooper, 1997 ; see Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The Nox‐dependent ROS production may be supported by impaired ROS degradation. Interestingly, phosphoinositolglycans prepared from plants and bacteria have been shown to inhibit the peroxidase and haeme‐containing catalase in non‐competitive fashion ( Thomasz et al ., 2007 ). Strikingly, similar phosphoinositolglycan structures may be released from the GPI anchors of GPI‐proteins, such as Gce1 and CD73, upon lipolytic cleavage by the GPI‐PLC ( Stralfors, 1997 ; Jones and Varela‐Nieto, 1998 ), which is apparently activated by palmitate, glimepiride and H 2 O 2 ( Müller et al ., 1993 , 1994a , 2008c ; Movahedi and Hooper, 1997 ; see Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Theses enzymes belong to oxidoreductases class which has different roles in some metabolic pathways of aerobic organisms. They exist in animal and plant tissues as well as in microorganisms, Peroxidases catalyze the oxidation -reduction reaction that occurs between H 2 O 2 and various reductants [21,22] . Hydrogen peroxide is (H 2 O 2 ) a signaling molecule that has an important role in the regulation of many biological processes [23,24] .…”
Section: -Introductionmentioning
confidence: 99%
“…Previous finding reported that Inositol phosphoglycan-like compounds decrease the activity of the two enzymes including peroxidases and catalase, with increasing the concentration of cellular H 2 O 2 . Although high concentrations of H 2 O 2 consider toxic, but slightly increase in H 2 O 2 level is associated to several metabolic pathways [22] .…”
Section: -Introductionmentioning
confidence: 99%